2022
DOI: 10.3389/fped.2021.796725
|View full text |Cite
|
Sign up to set email alerts
|

Different Reaction Patterns of Caregivers of Children With Imperforate Anus: A Latent Profile Analysis

Abstract: AimThis study aimed to explore how different dimensions of caregivers' reaction shape their caring experience, and the factors associated with different reaction patterns.DesignA second analysis of a multisite cross-sectional study were conducted. Caregivers of children with imperforate anus (IA) were enrolled in three tertiary children's hospitals in Eastern China between November 2018 and February 2019.MethodsThe caregiver's experience, stigma feeling, social support level and perception of uncertainty were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A previous study on 229 caregivers of children with imperforate anus showed that only 4.8% belonged to the high-benefit group. 30 However, a study on informal caregivers of older adults in America indicated that the high-benefit group was larger, accounting for more than 30% of the participants. 31 The difference in the number of individuals attributed to the high-benefit group was large among different studies and accounted for only 7.7% in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study on 229 caregivers of children with imperforate anus showed that only 4.8% belonged to the high-benefit group. 30 However, a study on informal caregivers of older adults in America indicated that the high-benefit group was larger, accounting for more than 30% of the participants. 31 The difference in the number of individuals attributed to the high-benefit group was large among different studies and accounted for only 7.7% in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As caregiving time increased, long-term caregivers felt more burdened by caregiving than by the benefit from it. 30 A longitudinal study of patients with multiple sclerosis found that the level of BF was positively correlated with diagnosis time 45 ; that is, the longer the diagnosis time, the higher the BF level. Cassidy found that caregiver benefit perception has two peaks: one at 7–12 months and the other at 13–24 months.…”
Section: Discussionmentioning
confidence: 99%